Bryophytes of Europe Traits (BET) data set: A fundamental tool for ecological studies. (27th March 2023) - van Zuijlen, Kristel; Nobis, Michael P.; Hedenäs, Lars; Hodgetts, Nick; Calleja Alarcón, Juan A.; Albertos, Belén; Bernhardt‐Römermann, Markus; Gabriel, Rosalina; Garilleti, Ricardo; Lara, Francisco; Preston, Chris D.; Simmel, Josef; et al.
Abstract: Bryophytes are a diverse group of organisms with unique properties, yet they are severely underrepresented in plant trait databases. Building on the recently published European Red List of bryophytes and previous trait compilations, we present the Bryophytes of Europe Traits (BET) data set, including biological traits such as those related to life history, growth habit, sexual and vegetative reproduction; ecological traits such as indicator values, substrate and habitat; and bioclimatic variables based on the species' European range. The data set includes values for 65 traits and 25 bioclimatic variables, containing more than 135, 000 trait values with a completeness of 82.7% on average. The data set will enable future studies in bryophyte biology, ecology and conservation, and may help to answer fundamental questions in bryology. Abstract : We present the Bryophytes of Europe Traits (BET) data set, a trait compilation for 1, 816 species including 65 biological and ecological traits, and 25 bioclimatic variables based on the species' European range. The data set will enable future studies in bryophyte biology, ecology, conservation and vegetation science, and may help to answer fundamental questions in bryology.